The unique Cambro-Ordovician silicic large igneous province of NW Gondwana: Catastrophic melting of a thinned crust - Rodriguez, C. (2022)
Cambro–Ordovician silicic magmatism in the Central Iberian Zone of the Iberian Massif (Ollo de Sapo Formation, OSF) constitutes a voluminous and geochemically atypical magmatic event that formed preceding the breakup of the northern margin of Gondwana. To date, and due to uncommon geochemical signatures, such as a high Fe, Mg content compared to anatectic melts and the departing from the calc-alkaline trends, the origin of such magmatic event is not fully understood. Herein, we report a data-analysis of geochemistry linking magmas and source compositions. The analysis of the combined data from multiple studies ascribes the geochemistry of the OSF rocks to a combination of extensive melting of Ediacaran metasiliciclastic rocks and a Ca-rich component. It is hypothesized that fluids released by crystallization of mafic magmas contributed to partial melting of a thick metasedimentary pile represented by Ediacaran siliciclastic rocks. Such melting event gave rise to a mobile nebulite or migma, which was able to extrude and form the super-eruption or ‘‘flare-up” that characterizes Cambro-Ordovician silicic magmatism at the Gondwana margin. Fast, catastrophic crustal melting with large-scale restite entrainment, triggered by the influx of mafic magma-derived fluids, are considered the main cause of the unique features of this Cambro-Ordovician atypical silicic large igneous province of Gondwana.